Looking for Candida nivariensis and C. bracarensis among a large Italian collection of C. glabrata isolates: results of the FIMUA working group. Issue 3 (21st November 2012) - Esposto, M. C.; Prigitano, A.; Romeo, O.; Criseo, G.; Trovato, L.; Tullio, V.; Fadda, M. E.; Tortorano, A. M.; ,
Summary Two recently described pathogenic Candida species, C. nivariensis and C. bracarensis, share many phenotypic characteristics with C. glabrata and are easily misidentified as such. The aim of this study was to determine the occurrence of these cryptic species in Italy. One thousand yeast isolates collected in 14 Italian regions and identified as C. glabrata by phenotypic and biochemical methods were included in this study: 928 were screened on CHROMagar and 72 were analysed by a multiplex PCR. None of these cryptic species was identified despite the nationwide distribution and the variety of biological origin of the isolates.